2018
DOI: 10.4103/ija.ija_55_18
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ultrasound-guided bilateral subcostal transversus abdominis plane block and port-site infiltration with bupivacaine in laparoscopic cholecystectomy

Abstract: Background and Aims:Many patients experience moderate-to-severe pain after laparoscopic cholecystectomy. We aimed to compare the efficacy of ultrasound-guided bilateral subcostal transversus abdominis plane (TAP) block with port-site infiltration for post-operative analgesia after laparoscopic cholecystectomy.Methods:Patients undergoing elective laparoscopic cholecystectomy under general anaesthesia were divided into two groups of 40 each to receive ultrasound-guided bilateral subcostal TAP block (T) with 0.25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…21 In our study we found that differences in 24 hours VAS score was statistically significant. In study conducted by Suseela et al 22 with sample size of 40 in each group found ultrasound guided Subcostal TAP block is superior to port-site infiltration in providing post-operative analgesia after laparoscopic cholecystectomy with reduced pain scores(p<0.001) which is consistent with our study. Bhalekar et al reported lower VAS score in Subcostal TAP group than control group at 0hr (2.1 vs 4.2), 2hr (2.1 vs 4.2), 4hr (2.0 vs 4.1), 8hr (1.8 vs 4.0), 16hr (1.7 vs 3.9) and 24hr (1.5 vs 3.7) .…”
Section: Discussionsupporting
confidence: 92%
“…21 In our study we found that differences in 24 hours VAS score was statistically significant. In study conducted by Suseela et al 22 with sample size of 40 in each group found ultrasound guided Subcostal TAP block is superior to port-site infiltration in providing post-operative analgesia after laparoscopic cholecystectomy with reduced pain scores(p<0.001) which is consistent with our study. Bhalekar et al reported lower VAS score in Subcostal TAP group than control group at 0hr (2.1 vs 4.2), 2hr (2.1 vs 4.2), 4hr (2.0 vs 4.1), 8hr (1.8 vs 4.0), 16hr (1.7 vs 3.9) and 24hr (1.5 vs 3.7) .…”
Section: Discussionsupporting
confidence: 92%
“…[ 10 ] recommended the use of paracetamol or nonsteroidal anti-inflammatory drugs preoperatively and LA infiltration at port sites to curb pain after LC. The other modalities such as TAP[ 11 ] and OSTAP block[ 4 ] tried so far mostly cover the somatic component and pain from parietal peritoneum, but the visceral pain of dissection of the gallbladder from the liver bed is left uncovered. The paravertebral block affects both somatic and visceral pain[ 12 ] but has its own set of disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…Patient-controlled analgesia with opioids, port-site infiltration, intraperitoneal instillation with local anesthetics (LA), transversus abdominis plane (TAP) block,[ 3 ] and oblique subcostal transversus abdominis plane (OSTAP) block, paravertebral block have been tried. [ 4 ] Except paravertebral block, these techniques affect only somatic pain and can be inadequate in some cases. [ 2 ] Thus, the quest for a better analgesic modality is ongoing.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that TAP blocks performed by either blind or under ultrasound guidance are effective in providing analgesia in laparoscopic surgeries. [45789] Blind TAP blocks are performed after locating the triangle of Petit using the double pop loss of resistance technique. [12] It is associated with a high incidence of penetrative injuries and a higher failure rate.…”
Section: Discussionmentioning
confidence: 99%
“…[123] It is also used in laparoscopic surgeries to reduce postoperative pain and opioid requirements. [4567] Studies have examined the effectiveness of TAP block on relieving postoperative pain in laparoscopic procedures with conflicting results. Many studies showed reduction in postoperative pain and opioid consumption with TAP block.…”
Section: Introductionmentioning
confidence: 99%